Gamification in Education: Leveraging the Bamboozle App for Effective Summative Assessments in Seventh-Grade of Junior High School - Nurmawati; Siregar, Tasya Amelia Putri; Siregar, Muhammad Irfansyah; Harahap, Ibnu Alwi Zakrkasih (Universitas Pendidikan Ganesha, 2024)
Technological advancements encourage teachers to continuously innovate in creating engaging learning experiences to improve student learning outcomes. However, during the implementation of the Fikih Ibadah lesson in seventh-grade classes, the researcher identified student demotivation that affected their interest, engagement, and active participation in the learning process. This study aims to describe the planning, implementation, and outcomes of summative assessments using the Bamboozle application in seventh-grade classes. The study employs a qualitative approach with a field research design. Data were collected through interviews with teachers, students, and school principals, as well as observations and documentation. The collected data were analyzed using a descriptive qualitative analysis technique, including data reduction, data presentation, and conclusion drawing. The findings indicate that the planning of summative assessments using the Bamboozle app involved preparing learning materials, assessment instruments, and implementation strategies. The execution of the assessment was effective, with increased student participation during the learning process. Based on interviews, students showed higher enthusiasm toward app-based assessments compared to conventional assessment methods. Moreover, the implementation of this approach successfully enhanced students' motivation, interest, and engagement in Fikih Ibadah lessons. The study concludes that the use of the Bamboozle app in summative assessments can serve as an effective innovation to improve learning quality, particularly in boosting student motivation and engagement.